2014
DOI: 10.1016/j.chb.2014.03.060
|View full text |Cite
|
Sign up to set email alerts
|

Personality and Internet usage: A large-scale representative study of young adults

Abstract: a b s t r a c tStudies that have examined the relationship between personality and Internet use so far were largely conducted on the basis of small, non-representative samples, and have yielded conflicting results. In the current study we estimate the relationship of the Big 5 personality traits and Internet use in a large nationally representative U.S. sample of over 6900 young adults with average age of 26. Our results suggest that global Internet use is positively related to Extraversion, Neuroticism, and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
57
4
8

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(82 citation statements)
references
References 47 publications
(123 reference statements)
13
57
4
8
Order By: Relevance
“…This finding stands in contrast to previous studies (Amichai-Hamburger, 2002;Amichai-Hamburger & Ben-Artzi, 2003;Amichai-Hamburger, Wainapel, & Fox, 2002, Mark & Ganzach, 2014, which suggested neuroticism was significantly related to Internet use. This difference can be due to the fact that the current study focused on ICT (Information and Communication Technology) in general and not only on Internet use, as was examined previously.…”
Section: Dependent Variablecontrasting
confidence: 56%
See 2 more Smart Citations
“…This finding stands in contrast to previous studies (Amichai-Hamburger, 2002;Amichai-Hamburger & Ben-Artzi, 2003;Amichai-Hamburger, Wainapel, & Fox, 2002, Mark & Ganzach, 2014, which suggested neuroticism was significantly related to Internet use. This difference can be due to the fact that the current study focused on ICT (Information and Communication Technology) in general and not only on Internet use, as was examined previously.…”
Section: Dependent Variablecontrasting
confidence: 56%
“…The findings indicate that the more extroverted and open to experience students are, the higher their ICT use. This finding was not unanticipated, as past studies have already shown that extroversion is strongly associated with Internet use (Amichai-Hamburger, 2002;AmichaiHamburger & Ben-Artzi, 2003;Amichai-Hamburger et al, Wainapel, & Fox, 2002;Mark & Ganzach, 2014), and with social networks use (Aharony, 2013;Gosling et al, 2011;Wilson et al, 2010;Zywica & Danowski, 2008). Considering openness to experience, Ross et al (2009) found that heavy users of social networking sites have higher levels of openness to experience.…”
Section: Dependent Variablementioning
confidence: 52%
See 1 more Smart Citation
“…Walaupun sebilangan pengguna kerap menggunakan laman sosial untuk mendedahkan maklumat peribadi (Fogel & Nehmad, 2009) namun, kedua-dua personaliti E-ISSN: 2289-1528 https://doi.org/10.17576/JKMJC-2018-3403-03 tidak cenderung untuk mencari maklumat atau mengintip aktiviti individu lain. Tambahan lagi, kedua-dua personaliti menggunakan laman sosial untuk tujuan interaksi, hiburan, akademik dan pendedahan kendiri (Hollenbaugh & Ferris, 2014;Mark & Ganzach, 2014 Komunikasi dengan rakan lama 30.0 (9) 70.0 (21) 60.0 (18) 40.0 (12) 5.…”
Section: Pengenalanunclassified
“…A number of studies have been conducted to examine personality traits and motivations in relation to ICT use, but their target population has always been focusing on participants who are not from the education major or the teaching profession (Norsiah et al, 2015;Mark & Ganzach, 2014;Wehrli, 2008). Besides, the current literature to date has not covered the Malaysian context (Norsiah et al, 2015), especially involving the ESL teachers.…”
Section: Introductionmentioning
confidence: 99%